Determination of Herbage Yield and Quality of Some Italian Ryegrass Varieties in Sivas Ecological Conditions - İlker YÜCE; Muhammed TATAR; Kağan KÖKTEN; Meliha Feryal SARIKAYA; Yeter ÇİLESİZ; Tolga KARAKÖY (ISPEC Journal of Agricultural Sciences, 2024)
Italian ryegrass is a forage plant that can grow rapidly vegetatively, can take at least two cuts in suitable ecologies, and has a tall plant height. Italian ryegrass, an annual forage crop, is rich in minerals, protein and water-soluble carbohydrate content, good palatability, digestibility and metabolic energy value are quite high compared to herbage of medium pasture quality. Italian ryegrass is a plant that has the potential to be a solution to the roughage needs of farm animals in Turkey. In this context, the aim of this study is to determine the Italian ryegrass variety or varieties with high yield and quality suitable for Sivas ecology. Twenty-one Italian ryegrass varieties (Master, Quickston, Big Boss, Koga, Venüs, Braulio, Jivet, Medoacus, Excellent, Tornado, İlkadım, Caramba, Kartetra, Efe-82, Trinova, Hellen, Devis, Vallivert, Teanna, Rambo, Zeybek-19) were used as plant material in the experiment. Experiment was conducted at Sivas Science and Technology University, Faculty of Agricultural Sciences and Technology, Agricultural Ar&Ge Center trial area in 2022-2023 growing season. According to the data obtained, the differences between Italian ryegrass varieties were found to be statistically significant in terms of plant height, green and dry herbage yields. Plant height, green and dry herbage yields ranged between 115.0-130.7 cm, 1407-3240 kg da-1 and 392-976 kg da-1, respectively. In terms of quality parameters of varieties, differences were also significant. The values were 11.18-14.73% for crude protein rates, 6.57-12.43% for crude ash rates, 32.9-37.7% for ADF (Acid detergent fiber) rates, 61.6-65.4% for NDF (Neutral detergent fiber) rates, 59.55-62.76% for DMD (Digestible dry matter) rates, 1.84-1.95% for DMI (Dry matter intake) rates, and 84.76-94.42 for RFV (Relative feed value) values. Among the Italian ryegrass varieties used in the research, it was determined that Excellent variety performed well in terms of herbage yield, and İlkadım, Master and Kartetra varieties performed well in Sivas conditions in terms of herbage quality.